Plankton Community Structure In Halmahera Barat Coastal Zone - Tamrin; Joshian Nicolas William Schaduw; Haryani Sambali; Adnan Sjaltout Wantasen; Desy Maria Helena Mantiri; Rene Charles Kepel; Winda Mercedes Mingkid; Ockstan Jurike Kalesaran; Nurhalis Wahidin; Muhammad Aris (Jurnal Ilmiah Platax, 2024)
Research on plankton organisms in supporting aquatic resource management is very important to do. This study aims to see the structure of the plankton community in the coastal waters of West Halmahera Regency. There were 9 sampling sites, namely the waters of Toniku (TO), Tewe (TW), Dodinga (DG), Tuada (TU), Porniti (PR), Payo (PA), Bobo (BO), Sahu (SH), and Ibu (IB). Plankton observations used the Census-SRC method. The parameters observed were abundance, diversity index, uniformity index, and dominance index. The results showed that the highest phytoplankton abundance was found in the TO area, namely 1.7 x 107 cells/m3 and the lowest was 4.1 x 106 cells/m3 in the PR area. The highest phytoplankton diversity index was found in the PR area, namely 2.075 and the lowest was 1.429 in the IB area. The highest uniformity index of phytoplankton was found in the PR area, namely 0.901 and the lowest was 0.624 in the BO and DG areas. The highest phytoplankton dominance index was found in the IB area, namely 0.350 and the lowest was 0.138 in the PR area. The highest zooplankton abundance was found in the DG area at 2.0 x 106 cells/m3 and the lowest was 3.3 x 105 cells/m3 in the IB area. The highest zooplankton diversity index was found in the TU area, namely 1.981 and the lowest was 1.516 in the IB area. The highest uniformity index of zooplankton was found in the IB area, namely 0.942 and the lowest was 0.761 in the DG area. The highest zooplankton dominance index was found in the BO area, namely 0.266 and the lowest was 0.167 in the TU area. The conclusion of this study revealed that the most common type of plankton found was Bacillariophyceae. While the diversity value shows moderate diversity, the uniformity value shows a high level of uniformity, and the dominance value shows low-moderate dominance. Keywords: Diversity index; Uniformity index; Dominance index; Abundance; Plankton Abstrak Penelitian tentang organisme plankton dalam mendukung pengelolaan sumberdaya perairan sangat penting untuk dilakukan. Penelitian ini bertujuan melihat struktur komunitas plankton perairan kawasan pesisir Kabupaten Halmahera Barat. Terdapat 9 lokasi sampling, yaitu perairan Toniku (TO), Tewe (TW), Dodinga (DG), Tuada (TU), Porniti (PR), Payo (PA), Bobo (BO), Sahu (SH), dan Ibu (IB). Pengamatan plankton menggunkan metode Sensus-SRC. Parameter yang diamati adalah kelimpahan, indeks keragaman, indeks keseragaman, dan indeks dominansi. Hasil penelitian menunjukan kelimpahan fitoplankton tertinggi terdapat di kawasan TO yaitu 1,7 x 107 Sel/m3 dan terendah 4,1 x 106 Sel/m3 di kawasan PR. Indeks keragaman fitoplankton tertinggi terdapat di kawasan PR yaitu 2,075 dan terendah 1,429 di kawasan IB. Indeks keseragaman tertinggi fitoplankton terdapat di kawasan PR yaitu 0,901 dan terendah 0,624 di kawasan BO dan DG. Semetara indeks dominansi fitoplankton tertinggi terdapat di kawasan IB yaitu 0,350 dan terendah 0,138 di kawasan PR. Kelimpahan zooplankton tertinggi terdapat di kawasan DG yaitu 2,0 x 106 Sel/m3 dan terendah 3,3 x 105 Sel/m3 di kawasan IB. Indeks keragaman zooplankton tertinggi terdapat di kawasan TU yaitu 1,981 dan terendah 1,516 di kawasan IB. Indeks keseragaman tertinggi zooplankton terdapat di kawasan IB yaitu 0,942 dan terendah 0,761 di kawasan DG. Semetara indeks dominansi zooplankton tertinggi terdapat di kawasan BO yaitu 0,266 dan terendah 0,167 di kawasan TU. Kesimpulan penelitian ini mengungkapkan jenis plankton yang paling banyak ditemukan adalah Bacillariophyceae. Sementara nilai keragaman menunjukkan karagaman sedang, nilai keseragaman menunjukkan tingkat kesergaman tinggi, dan nilai dominasi menunjukkan dominansi rendah – sedang. Kata kunci: Indeks keragaman; Indeks keseragaman; Indeks dominansi; Kelimpahan; Plankton.